What is the best approach for preventing recruitment to terrorism? Findings from ABM experiments in social and situational prevention. Issue 2 (21st February 2022) - Weisburd, David; Wolfowicz, Michael; Hasisi, Badi; Paolucci, Mario; Andrighetto, Giulia
Abstract: Research Summary: This study uses agent‐based models (ABMs) to compare the impacts of three different types of interventions targeting recruitment to terrorism—community workers at community centers; community‐oriented policing; and an employment program for high‐risk agents. The first two programs are social interventions that focus on de‐radicalization and changing the dispositions of agents in the model, whereas the employment program focuses on "deflection" and represents a situational/opportunity reducing approach to prevention. The results show significant impacts of the community worker and community policing interventions on radicalization but no significant impact on recruitment. In contrast, the employment intervention had a strong and significant impact on recruitment, but little impact on radicalization. Policy Implications: Our ABM simulations challenge the reliance of existing programs to reduce recruitment to terrorism on counter and de‐radicalization approaches. Instead they suggest that policy makers should focus more attention on deflection and opportunity reduction. At the same time, our ABMs point to the salience of social interventions focusing on risk and protective factors for reducing radicalization in society.